Suppose we have the simple linear model $$\mathbf{y} = \beta_0 \mathbf{1} + \beta_1 \mathbf{x} + \boldsymbol{\epsilon},$$ with $\mathrm{E}[\boldsymbol{\epsilon}] = \mathbf{0}$ and $\mathrm{Var}[\boldsymbol{\epsilon}] = \sigma^2 \mathbf{I}$. The least squares estimator for $\beta_1$ is $$\hat{\beta}_1 = \frac{(\mathbf{x} - \bar{x}\mathbf{1})^T(\mathbf{y} - \bar{y}\mathbf{1})}{\|\mathbf{x} - \bar{x}\mathbf{1}\|^2}.$$ For this problem, we are treating $\mathbf{y}$ as a random vector (and so $\bar{y}$ is a random variable), so we have $\mathrm{E}[\mathbf{y}] = \beta_0 \mathbf{1} + \beta_1 \mathbf{x}$ (so for each response we have $\mathrm{E}[y_i] = \beta_0 + \beta_1 x_i$), and $\mathrm{E}[\bar{y}] = \beta_0 + \beta_1 \bar{x}$. In addition, we have $\mathrm{Var}[y_i] = \sigma^2$ for all $i$ and $\mathrm{Var}[\bar{y}] = \sigma^2 / n$.
Assuming that $\mathrm{E}[\hat{\beta}_1] = \beta_1$, we want to show that $$\mathrm{Var}[\hat{\beta}_1] = \frac{\sigma^2}{\|\mathbf{x} - \bar{x}\mathbf{1}\|^2}.$$ To start, it's helpful to re-write $\hat{\beta}_1$ as $$\hat{\beta}_1 = \frac{1}{\|\mathbf{x} - \bar{x}\mathbf{1}\|^2} \sum_{i=1}^n (x_i - \bar{x})(y_i - \bar{y}).$$ Again, we emphasize that the only sources of randomness in this are $y_i$ and $\bar{y}$ (which are in turn random because of $\epsilon_i$.)
Here is what I did: we have $$ \begin{align*} \mathrm{Var}[\hat{\beta}_1] &= \mathrm{Var} \left[\frac{1}{\|\mathbf{x} - \bar{x}\mathbf{1}\|^2} \sum_{i=1}^n (x_i - \bar{x})(y_i - \bar{y}) \right] \\ &= \frac{1}{\|\mathbf{x} - \bar{x}\mathbf{1}\|^4} \cdot \mathrm{Var} \left[ \sum_{i=1}^n (x_i - \bar{x})(y_i - \bar{y})\right] \\ &= \frac{1}{\|\mathbf{x} - \bar{x}\mathbf{1}\|^4} \sum_{i=1}^n \mathrm{Var} \Big[ (x_i - \bar{x})(y_i - \bar{y}) \Big] \\ &= \frac{1}{\|\mathbf{x} - \bar{x}\mathbf{1}\|^4} \sum_{i=1}^n (x_i - \bar{x})^2 \cdot \mathrm{Var} \big[ (y_i - \bar{y}) \big] \\ &= \frac{1}{\|\mathbf{x} - \bar{x}\mathbf{1}\|^4} \sum_{i=1}^n (x_i - \bar{x})^2 \cdot \Big( \mathrm{Var}[y_i] + \mathrm{Var}[\bar{y}]\Big) \\ &= \frac{1}{\|\mathbf{x} - \bar{x}\mathbf{1}\|^4} \sum_{i=1}^n (x_i - \bar{x})^2 \cdot \Big( \sigma^2 + \sigma^2 / n \Big) \\ &= \frac{n+1}{n} \cdot \frac{\sigma^2}{\|\mathbf{x} - \bar{x}\mathbf{1}\|^2}. \end{align*} $$ So I'm close to the answer, but it's off by a factor of $(n+1)/n$.
When looking to see what others did, it seems that the trick is to get rid of the $\bar{y}$ in the equation altogether, since $$ \sum_{i=1}^n (x_i - \bar{x})(y_i - \bar{y}) = \sum_{i=1}^n (x_i - \bar{x})y_i + \underbrace{\sum_{i=1}^n (x_i - \bar{x}) \bar{y}}_{= ~0} = \sum_{i=1}^n (x_i - \bar{x}) y_i. $$ Once this is done, the extra variance added by $\bar{y}$ is gone, and we get the correct answer. I get that, but I don't understand why the way I did it is incorrect, and leaving it in gives the incorrect answer.
What is wrong with leaving it in? Did I make a mistake with my calculations?